Share repurchase and stock price synchronicity - Chenghao Huang; Zhi Jin (China Journal of Accounting Studies (CJAS), 2024)
This paper explores the impact of open market share repurchases (OMR) on stock price synchronicity. We find that share repurchases significantly enhances the information content of stock prices, reflected in reduced price synchronicity. The mechanism includes repurchases drawing investor attention, encouraging more idiosyncratic information disclosures, and increasing media coverage. This effect is more pronounced in firms with high information asymmetry, those leveraging repurchases for reputation, or emphasizing R&D. Further analysis reveals that characteristics and execution of repurchase programmes impact differently.Overall, OMR acts as an effective signal, attracting attention from external market participants and improving the firm's informational environment.
Keywords: 650; information environment; institution reform; Share repurchase; stock price synchronicity